MAPKAP kinase 3 suppresses Ifng gene expression and attenuates NK cell cytotoxicity and Th1 CD4 T‐cell development upon influenza A virus infection. Issue 10 (16th June 2014) - Köther, Katharina; Nordhoff, Carolin; Masemann, Dörthe; Varga, Georg; Bream, Jay H.; Gaestel, Matthias; Wixler, Viktor; Ludwig, Stephan
Abstract : MK2 and MK3 are downstream targets of p38 and ERK1/2. They control the mRNA stability of several inflammatory cytokines, including TNF‐α and IL‐10. Whereas MK2 is expressed ubiquitously, the expression of MK3 is restricted to muscle, liver, and heart tissues and T and NK cells. Using Mk ‐deficient and wild‐type (WT) mice, we demonstrated an inhibitory effect of MK3, but not of MK2, on interferon (IFN)‐γ expression in T and NK lymphocytes. The results provided evidence that the inhibitory effect of MK3 is based on negative feedback phosphorylation of p38 and ERK1/2, which causes decreased binding of Stat4 to the IFN‐γ promoter and reduced expression of IFN‐γ mRNA and protein. Consequently, all Mk3 –/– mice challenged with the Th1‐inducing influenza A virus (IAV) survived the WT LD50 virus dose. The reduced disease severity in the Mk3 –/– mice was accompanied by a >10‐fold reduction in viral lung titer and an increase in the number of activated NK cells and enhanced Th1 activation of CD4 T cells. Thus, our data describe the protein kinase MK3 as a novel regulator of the innate and adaptive immune responses.—Köther, K., Nordhoff, C., Masemann, D., Varga, G., Bream, J. H., Gaestel, M., Wixler, V., Ludwig, S., MAPKAP kinase 3 suppresses Ifng gene expression and attenuates NK cell cytotoxicity and Th1 CD4 T‐cell development upon influenza A virus infection. FASEB J. 28, 4235‐4246 (2014). www.fasebj.org